PENGEMBANGAN MEDIA PRIMAFORM UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATERI FPB DAN KPK DI SEKOLAH DASAR - Pasambuna, Sri Yunarni; Abdullah, Gamar; Aries, Nur Sakinah; Marshanawiah, Andi; Arif, Rifda Mardian (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop Primaform learning media that meets the criteria of feasibility, practicality, and effectiveness in learning Mathematics to improve students' problem-solving abilities in FPB and KPK materials in class V of SDN 9 Kabila. The method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analyze, design, development, implement, and evaluate. The feasibility of Primaform media was tested through expert validation, with an average percentage result of 89%, which is included in the